Diseño Universal para el Aprendizaje y la Educación Básica Intensiva del Colegio Oscar Efrén Reyes de la ciudad de Baños de Agua Santa, durante el año lectivo 2021-2022 - Armendariz Rodriguez, Mayra Veronica (2022)
ABSTRACT: This research stems from the problems found in the institution, where students are in unfinished schooling and teachers do not know what methodological strategies to apply to strengthen the teaching-learning process. Its objective was "To prepare a guide for the implementation of the Universal Design for Learning for teachers of intensive basic education of the subjects of: Language and Literature, Mathematics and Social Studies of the Oscar Efrén Reyes School of the City of Baños de Agua Santa for the first two months of the second semester of the 2021-2022 school year. Its methodology was with a quantitative approach, with a quasi-experimental design, cross-sectional, field study and documentary bibliography, with descriptive and explanatory level or scope, using deductive, inductive methods, having a population of 46 research subjects comprised of 6 teachers and 40 students of the upper basic education sublevel, to whom a questionnaire was applied as a data collection instrument. It should be noted that the results obtained through the surveys applied to teachers and students, 85% of the teachers do not use methodological strategies applied with the DUA to provide quality education to adults with unfinished schooling, by students of a total of 40, it is estimated that 80% do not perceive integrative or inclusive education in terms of infrastructure, teaching resources, and teaching methodologies that are not adequate to optimize types of learning. To the conclusions that were reached after the results, on the part of the teachers they do not know how the DUA works and its application in the microcurricular planning to improve and strengthen the teaching-learning process, allowing to provide multiple forms of presentation, action and expression, and of application, through the generation and use of strategies, activities and resources for the due inclusion of people focused on unfinished schooling; while on the part of the students it is concluded that they are not attended to in a timely manner and adjusted to the reality of their educational needs and focused on the fact that they are adults with unfinished schooling and that their type of learning is different, where the adequate teaching methods and resources so that the information obtained is not captured in an optimal way.